2020
DOI: 10.9734/jocamr/2020/v11i230181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nephrotoxic and Hepatotoxic Potential of Artesunate in Malaria Patients

Abstract: Aim: To evaluate the nephrotoxic and hepatotoxic potentials of artesunate in humans. Place and Duration of Study: Department of Biochemistry, Michael Okpara University of Agriculture, Umudike, Abia State, Nigeria, between November and December 2019. Methodology: 70 blood samples were collected from 35 normal individuals (control group), and 35 malaria patients treated with parenteral artesunate (treatment group). These were analyzed for biochemical parameters, including blood urea nitrogen (BUN), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Early detection of diabetes mellitus, lifestyle changes, dietary restriction, and monitoring of blood glucose levels and organ functions including medical interventions remain the major steps towards successful management of diabetes mellitus (Ibeh et al, 2020). While some conventional therapies may not be harmful to the kidneys or liver, studies have shown the beneficial effect of medicinal plants in reducing kidney and liver damage, either alone or in combination with conventional therapy (Nwankpa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of diabetes mellitus, lifestyle changes, dietary restriction, and monitoring of blood glucose levels and organ functions including medical interventions remain the major steps towards successful management of diabetes mellitus (Ibeh et al, 2020). While some conventional therapies may not be harmful to the kidneys or liver, studies have shown the beneficial effect of medicinal plants in reducing kidney and liver damage, either alone or in combination with conventional therapy (Nwankpa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%